Minimally invasive approach for treating voluminous periapical cysts of the frontal maxillary teeth - Raluca A. Dragomir; Andrada R. Doscas; Florin Sava; Andrei Nicolau; Victor-Vlad Costan (Amaltea Medical Publishing House, 2020)
The aim. Treatment of a large cystic lesion in the maxillary bone involving the nasal cavity and the sinus may be challenging. The traditional approach represented by simple enucleation could irreversibly damage the anatomical structures, therefore, we aimed to evaluate the value of decompression prior to the actual surgical procedure. Materials and methods. Our treatment strategy focused first on minimizing the lesion by decompression and then performing enucleation. Results. Follow-up cone beam computed tomography scans showed progressive bone healing and the treatment results were satisfying, with low morbidity rate and no recurrence.